2017
DOI: 10.1074/jbc.m117.776112
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-independent Role of Cyclin D3 in Host Restriction of Influenza Virus Infection

Abstract: To identify new host factors that modulate the replication of influenza A virus, we performed a yeast two-hybrid screen using the cytoplasmic tail of matrix protein 2 from the highly pathogenic H5N1 strain. The screen revealed a high-score interaction with cyclin D3, a key regulator of cell cycle early G1 phase. M2-cyclin D3 interaction was validated through GST pull-down and recapitulated in influenza A/WSN/33-infected cells. Knockdown of Ccnd3 by small interfering RNA significantly enhanced virus progeny tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 82 publications
1
41
0
Order By: Relevance
“…However, the role of BST-2 in limiting IAV release has been disputed (Watanabe et al 2011), perhaps due to IAV strain-specific susceptibility to BST-2 restriction. This interaction was confirmed by orthogonal assays, and using chimeric and truncated M2, the regions Fan et al (2017)] involved in BST-2 downregulation were proposed to be within the M2 extracellular and TMDs.…”
Section: Host Interactionsmentioning
confidence: 67%
See 1 more Smart Citation
“…However, the role of BST-2 in limiting IAV release has been disputed (Watanabe et al 2011), perhaps due to IAV strain-specific susceptibility to BST-2 restriction. This interaction was confirmed by orthogonal assays, and using chimeric and truncated M2, the regions Fan et al (2017)] involved in BST-2 downregulation were proposed to be within the M2 extracellular and TMDs.…”
Section: Host Interactionsmentioning
confidence: 67%
“…Results from another yeast two-hybrid screen using the M2 cytoplasmic tail as a bait have identified the human cell cycle regulator cyclin D3 as a binder, and their interaction has been confirmed in infected cells by immunoprecipitation assays (Fan et al 2017). Using siRNA-mediated knockdown of cyclin D3 expression, the study proposed that cyclin D3 is a negative modulator of IAV infection, competing with M1 for binding to M2 in transfected cells and therefore disrupting the important M1-M2 interaction in the context of an IAV infection.…”
Section: Host Interactionsmentioning
confidence: 97%
“…It has been reported that SLD5 interacts with Psf1, Psf2, and Psf3 (Choi et al, 2007;Gouge & Christensen, 2010;Joshi et al, 2016;Takayama et al, 2003). Previous studies have shown that IAV infection induces host cell G0/G1 phase arrest (Fan et al, 2017;He et al, 2010;Jiang et al, 2013). Some bacterial virus can shut off host DNA replication to arrest host growth (Belley et al, 2006;Seco et al, 2013;Yano & Rothman-Denes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the strength of the cell cycle arrest varies among different influenza virus strains, it is possible that more than one viral protein is involved in this process in certain strains (Fan et al, 2017;He et al, 2010;Jiang et al, 2013;Wang et al, 2012). The NS1 protein from WSN virus has been shown to arrest host cell cycle mainly through interfering with the RhoA/pRb signalling cascade (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This approach reduces the likelihood of resistance since host genes are unlikely to mutate as fast as viral ones. Many scientists have used the yeast two-hybrid system to identify host interactors of individual viral proteins: NS1 [144][145][146][147][148][149][150][151][152][153][154][155][156][157][158], NS2 [129,144,[159][160][161], NP [162][163][164][165][166][167][168], PA [169][170][171][172], PB1 [173], PB2 [174], NA [175], M1 [176][177][178][179], M2 [180][181][182][183][184] and PB1-F2 [185][186][187][188][189]. Several studies applied the two-hybrid syste...…”
Section: The Yeast Saccharomyces Cerevisiae: a Powerful System For Idmentioning
confidence: 99%